2003
DOI: 10.1046/j.0902-0055.2002.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet responses and anaphylaxis‐like shock induced in mice by intravenous injection of whole cells of oral streptococci

Abstract: Intravenous injection of lyophilized whole cells of various oral streptococcal strains into muramyldipeptide (MDP)-primed C3H/HeN mice induces rapid anaphylactoid shock. Here we examined the mechanism underlying this shock. In non-primed mice, Streptococcus intermedius K-213K (SiK213) and Streptococcus constellatus T21 (ScT21) produced little or no sign of shock. In MDP-primed mice, SiK213 caused lethal shock, while ScT21 only had a weak effect. SiK213 induced decreases in blood platelets and 5-hydroxytryptami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…In combination with agonists for TLR2, TLR4 and TLR9, MDP induced marked synergistic pro-inflammatory cytokine secretion in human monocytic cells (Yang et al, 2001;Fritz et al, 2005;Uehara et al, 2005). Moreover, MDP-primed mice were hypersensitive to intravenous injections of Salmonella LPS and lyophilized whole cells of S. intermedius or S. constellatus (Takada and Galanos, 1987;Ohba et al, 2004). A recent report showing that the incubation of cells with MDP alone caused a significant expression of TNF-a mRNA but minimal production of TNF-a suggested that the majority of TNF-a mRNA induced by MDP alone is not translated into protein (Wolfert et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In combination with agonists for TLR2, TLR4 and TLR9, MDP induced marked synergistic pro-inflammatory cytokine secretion in human monocytic cells (Yang et al, 2001;Fritz et al, 2005;Uehara et al, 2005). Moreover, MDP-primed mice were hypersensitive to intravenous injections of Salmonella LPS and lyophilized whole cells of S. intermedius or S. constellatus (Takada and Galanos, 1987;Ohba et al, 2004). A recent report showing that the incubation of cells with MDP alone caused a significant expression of TNF-a mRNA but minimal production of TNF-a suggested that the majority of TNF-a mRNA induced by MDP alone is not translated into protein (Wolfert et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…32,33 LPS has also been shown to inhibit human platelet aggregation stimulated by agonists by inhibiting phosphoinositide breakdown and intracellular Ca ϩϩ mobilization. 34 Furthermore, LPS triggers the production of several proinflammatory cytokines (eg, TNF, IL-1) and the adherence of monocytes to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of whole cells of streptococci (Gram-positive bacteria) also induces ALS [8]. Interestingly, the induction of both LPS-ALS and Streptococcus-ALS involves activation of platelets followed by their degradation in the lung, liver, and/or circulation [9,10], and this platelet response is induced by activation of the lectin pathway in the complement system [8,11,12]. In the Klebsiella O3 LPS molecule, the mannose homopolymer structure within the O-antigen region is important for stimulation of the lectin pathway [12].…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with MDP augments both LPS-ALS and endotoxin shock in mice, including C3H/HeJ mice [1,2,7]. Injection of whole cells of streptococci (Gram-positive bacteria) also induces ALS [8]. Interestingly, the induction of both LPS-ALS and Streptococcus-ALS involves activation of platelets followed by their degradation in the lung, liver, and/or circulation [9,10], and this platelet response is induced by activation of the lectin pathway in the complement system [8,11,12].…”
Section: Introductionmentioning
confidence: 99%